DEVELOPMENT OF LEARNING ACHIEVEMENT IN BIOLOGY AND CRITICAL THINKING ABILITY BY USING 4MAT LEARNING MANAGEMENT AND MIND MAPPING TECHNIQUE IN MATHAYOMSUKSA 5 STUDENTS - Kungam, Uraiwan; Yuenyong, Yupin (Journal of MCU Phetchaburi Review, 2023)
Abstract Critical thinking is a high-level thinking skill that is essential to life and important for work for now or even in the future. It is very important and necessary to cultivate the students which gives students the opportunity to practice critical thinking. Practice thinking rationally and being able to solve problems creatively. The researcher is therefore interested in conducting this research. The objectives are 1) To compare learning achievements in Biology subjects before and after using the 4MAT learning with mind mapping techniques of Mathayomsuksa 5 students. 2) To compare the critical thinking ability before and after using the 4MAT learning management method combined with the mind mapping technique of Mathayomsuksa 5 students. 3) To study the learning behavior of Mathayomsuksa 5 students receiving the 4MAT learning management method combined with the mind mapping technique. 4) To study the satisfaction of Mathayomsuksa 5 students toward the 4MAT learning management method combined with mind mapping techniques. The populations were Mathayomsuksa 5/1 students at PaDengvittaya School. Secondary Educational Service Area Office Phetchaburi. The first semester of 2022. The 44 students were selected by purposive sampling. The research tools were 1) A learning management plan using 4MAT learning management combined with a mind mapping technique. 2) A biology learning achievement test. The Reliability is 0.80. The Difficulty index is between 0.33-0.63. The Discriminant index is between 0.25-0.70. 3) Critical thinking ability test. The consistency index was 0.67-1.00. 4) Learning Behavior Observation Form 5) Satisfaction Questionnaire with 4MAT learning management combined with mind mapping technique. The statistics used were averaging. Standard deviation and T score. The research results were as follows: Students’ biology learning achievement scores obtained after learning the lessons were higher than that of before with a statistically significant difference at .05. Students’ critical thinking skill scores obtained after learning the lessons were higher than that of before with a statistically significant difference at .05. The results of the analysis of learning behaviors of Mathayomsuksa 5 students who received the 4MAT learning management method together with the mind mapping technique revealed the behaviors that appeared in the early stages of the experiment. Some students still lack participation in answering questions or expressing opinions. Lack of knowledge and understanding about 4MAT learning management, As a result, the first period of development in this area is quite slow, Interest and willingness to learn have exchanged knowledge with others and jointly discussed the conclusions correctly. The analysis results of the satisfaction of Mathayomsuksa 5 students toward the 4MAT learning management with mind mapping techniques. When considering each side in order of average from the most to the least. Overall, it was found that No. 1 in learning management. Ranked the second highest level in terms of benefits that students receive was at the highest level; the 3rd was the instructor at a high level, and the 4th was the learning management media. At a high level . The research findings the only way to manage 4MAT learning may make the Critical thinking ability of students not reach their full potential. Therefore, adding mind-mapping techniques to the learning process will help develop critical thinking abilities to be more effective. Keywords : Critical thinking, 4MAT teaching model, mind mapping technique